Demand respond management for industrial/residential load consumer - Goh, Kai Lun. (2012)
This project is a combine of 2 continuation project from 2010/11 semester 1, A1038-101 Demand Response Management for Staff Quarters at NTU, and A1028-101 Demand Response Management for Industrial Load Consumers. The project will be focusing on the testing out of the load shedding scheme which can be made similar to the existing Singapore interruptible load scheme and the time-of use (TOU) pricing scheme.